(untitled) (Ukrainian Journal of Ophthalmology, 2025)
In the current paper, we present an example case of persistent recurrent herpes zoster ophthalmicus with the development of chronic keratoconjunctivitis, corneal opacity, secondary eczema herpeticum and resistance both to antiviral drugs and to anti-allergic medications in a female patient with primary MBL deficiency. Particularly, we demonstrate how the elucidation of the causative immune deficiency and the related administration of specific replacement immunotherapy has become the cornerstone of the achievement of clinical success in the difficult-to-treat patient. Immunological tests demonstrated that the patient had a significantly reduced MBL level (167 ng/ml compared to a norm of 450 ng/ml), whereas other studied immune status characteristics where within normal range. We identified two pathological polymorphisms in the promoter and structural region of MBL-2 (particularly, –550 G/C and 221 C/G), which indicated that the patient had a primary MBL deficiency. It was the fact that the patient had the above genetic immunodeficiency disease that an atypical and unfavorable course of varicella zoster virus infection was associated in this case. The identification of primary MBL deficiency opened the door for new ways of therapy for the difficult-to-treat infectious disease through the specific replacement immunotherapy with the aim of improving immune control of the opportunistic agent through compensation of primary immunodeficiency.